Hungary's place on Eurasian rail land bridges and the eastern opening - Farkas, Z. Andrew; Pap, Norbert; Reményi, Péter (Hungarian Geographical Bulletin, 2017)
In the early 21st century the global financial crisis changed the economic position of many states, including the EU, which is only slowly recovering, and the quickly emerging economies of Asia. Several factors in global transportation have driven countries to fi nd alternative transport links and methods, including between Europe and Asia. Since 2010 government of Hungary has shift ed the focus of Hungarian foreign policy towards "the East", which can be perceived as an interest-based real policy. The above factors and Hungary's landlocked position gave a renewed impetus to the so-called Eurasian land bridge issue, which intends to connect Central and Eastern Europe and East Asia on land. As the authors argue, after comparing foreign strategies of CEE countries, "eastern opening" of Hungary is not a unique move in the region, neither is the renewed interest in rail land bridges. However, aft er examining all the possible land routes towards East Asia, the authors agree with those who see these routes as unsustainable in the short run. On the other hand, the moves of Chinese private and state-owned companies in Southeast Europe and CEE, the "New Silk Road" concept of the Chinese diplomacy and expansion of the Suez Canal may foresee the establishment of micro land-bridges from SEE ports via Hungary towards Western Europe, significantly shortening the routes and avoiding congested northwestern ports. In this regard Hungary may play an important role on these alternative routes providing economic and geopolitical benefits.